The Role of SQUAMOSA-PROMOTER BINDING PROTEIN-like (SPL) Transcription Factors in Plant Growth and Environmental Stress Response: A Comprehensive Review of Recent Advances - Runhua Bu; Zongqing Qiu; Jing Dong; Liqin Chen; Yu Zhou; Huilin Wang; Liangliang Hu (Horticulturae, 2025)
In plants, SPL is a distinct family of transcription factors. Its protein structure possesses a highly conserved SBP domain comprising two zinc finger structures and nuclear localization regions, and microRNAs (miR156) control the transcriptional expression of the majority of SPL genes. SPLs are key TFs in regulating organ morphogenesis, phase transition/floral induction, and yield-related traits in agronomic and horticultural crops. These biomolecules have been functionally characterized for their role in augmenting plant responses to abiotic and biotic stresses. Present research gaps and viewpoints are addressed herein. Using these extensive data, researchers can more comprehensively understand how SPL genes modulate agronomic features in different ways.